Neighbourhood characteristics and life satisfaction of individuals in lower-, middle-, and higher-income families in Canadian metropolitan areas - Mark W. Brown; Jonathan David Fonberg; Grant Schellenberg; River Yang (Economic and Social Reports, 2021)
While there are many studies that examine the relationships between neighbourhood characteristics and health outcomes, and between neighbourhood characteristics and neighbourhood satisfaction, the relationship between neighbourhood characteristics and subjective well-being, particularly life satisfaction, has received much less attention. The objective of this study is to fill this gap in order to help inform neighbourhood-based policy aimed at increasing well-being that is receiving increased attention.